Assessment of mental health care services in public health facilities: a study of socio-demographic characteristics, resource availability, and service delivery challenges in Kiambu County, Kenya - Kitui, Lichuma Eva; Mbaruk, Suleiman; Mogere, Dorminic (International Journal Of Community Medicine And Public Health, 2025)
Background: Despite the growing recognition of mental health as a critical component of overall well-being, mental health care services in public health facilities in Kiambu County, Kenya, remain under-researched and under-resourced. There is a lack of comprehensive data on the socio-demographic characteristics of healthcare workers, the availability of resources, and the challenges faced in delivering mental health services. This gap in knowledge hinders the development of effective policies and interventions to improve mental health care delivery and outcomes in the country. This study aimed to assess the state of mental health care and treatment services in public health facilities in Kiambu County, Kenya. Methods: This study employed a mixed-methods approach, collecting qualitative data through interviews and quantitative data via structured questionnaires from 165 healthcare professionals across 13 Kiambu County, Kenya public hospitals. Data analysis included descriptive statistics for quantitative data and thematic analysis for qualitative data. Results: The workforce is predominantly female (57.6%) and relatively young, with 40.6% aged 40-49. The majority hold degrees (65.5%) and have significant experience in mental health care, but there are gaps in specialized training and a shortage of psychiatrists (6.1%). Mental health care resources in Kiambu County are insufficient, with uneven staff distribution, a shortage of specialists, and limited training opportunities. Insufficient training opportunities, along with inadequate policy and funding support, further hinder service provision. Inadequate referral systems, a lack of essential equipment and medications, and poor budget allocation further strain service delivery. Conclusions: There are major gaps in specialized training, a shortage of psychiatrists, insufficient resources, and inadequate policy and funding support which significantly hinder effective mental healthcare service delivery.